A QUANTITATIVE ANALYSIS OF HUMAN RESOURCE MANAGEMENT PRACTICES AND THEIR IMPACT ON TEACHER PERFORMANCE IN SECONDARY EDUCATION INSTITUTIONS - Afrizal Afrizal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study examines how Human Resource Management (HRM) practices influence teacher performance in secondary education institutions. Teacher performance is a critical determinant of educational quality, student achievement, and overall school effectiveness. The research adopted a quantitative design with data collected from 384 teachers across multiple secondary schools. Standardized questionnaires assessed key HRM practices including recruitment and selection, training and development, performance appraisal, compensation, and employee involvement. Data analysis was conducted using SPSS 25.0, including descriptive statistics, reliability testing, correlation, and multiple regression analysis. Results show that HRM practices collectively have a significant positive impact on teacher performance. Training and development emerged as the strongest predictor, highlighting the importance of continuous professional learning for educators (Nguyen, 2021; Sari, 2020). Performance appraisal and employee involvement also significantly influenced performance, reflecting that regular feedback and participation in decision making enhance teacher effectiveness (Martins, 2019; Wijaya, 2022). Recruitment and selection practices were positively associated with performance, suggesting that hiring teachers with appropriate competencies and fit improves outcomes (Rohman, 2018). Compensation showed a moderate but significant influence, indicating that equitable rewards contribute to motivation and performance (Almeida, 2022). The findings underscore the need for school administrators to strengthen HRM practices to foster high performance among teachers. Practical implications include investing in targeted professional development, establishing transparent appraisal systems, promoting teacher participation, and aligning compensation with performance expectations to enhance educational quality and institutional success.